Mountain Hunting Land Lands of the Best Sirvan Region the Effects of the Erosion Process on Municipality (in the Case of Shamakhi Region) - ZH.Aliyev, Prof.Rans (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2018)
The aim of the study is to investigate the erosion of degraded brown soils used mainly under grain crops in the Shamakhi region, south-east of the Greater Caucasus, and erosion of moderately eroded species to the soil fertility parameters